Treatment of insomnia - effect of trazodone and hypnotics on sleep - Wichniak, Adam; Wierzbicka, Aleksandra Ewa; Jarema, Marek (Psychiatria polska, 2021)
Sedative antidepressants are commonly used drugs in the treatment of insomnia. However, some recommendations claim that only hypnotics have been proven effective in the treatment of sleep initiation and maintenance disorders. The aim of this article is to compare the effect of hypnotics and trazodone on sleep, and to analyse the evidence for the use of trazodone in the treatment of insomnia. Three studies investigated the effects of trazodone on sleep in primary insomnia, 5 studies on insomnia in the course of affective disorders and 6 studies on insomnia in other indications (PTSD, Alzheimer's disease, alcohol and opiate dependence, somatoform disorder, and insomnia during pregnancy). In the treatment of insomnia, trazodone is less effective than hypnotics in the treatment of sleep onset insomnia (i.e., disorders of falling asleep). For this indication it needs to be administered earlier than hypnotics, at least 1 hour before bedtime. It is, however, very effective in the treatment of sleep-maintenance insomnia, especially in patients with comorbid mental disorders or patients treated with activating antidepressants. Hypnotics and trazodone have the opposite effect on deep sleep. Trazodone increases the duration of deep sleep, which is associated with better sleep quality as assessed by patients. In contrast, hypnotics decrease slow-wave activityin sleep EEG, which is the biomarker of deep sleep. The main mechanism through which trazodone promotes sleep is its antagonistic effect on 5-HT2 serotonin receptors, while hypnotics are agonists of gamma-aminobutyric acid GABAA receptors, and other sedative antidepressants block H1 histamine receptors. This is associated with a low risk of weight gain, which is rare with trazodone treatment.